Traditional uses and phytopharmacology of Cirsium arvense: Bioprospecting potential of a weed from temperate biome - Acharya Balkrishna,, Hemant Sharma, Ankita Kukreti, Amita Kumari, Priyanka Saini, Vedpriya Arya,, Ashwani Kumar (Journal of Applied Pharmaceutical Science, 2024)
Cirsium arvense, a noxious weed of the Asteraceae family, has potential medicinal benefits. Traditionally, it has been used to cure ulcers, mouth infections, leukemia, dentalgia, canker sores, pharyngitis, and other ailments. Alkaloids, flavonoids, tannins, and diverse phytoconstituents are associated with its therapeutic potential. This review article sheds light on C. arvense’s taxonomy, geographical distribution, ethnomedicinal uses, and phytopharmacology. Despite its weedy nature, it has been a rich source of phytoconstituents, which is evident from its antimicrobial (against Gram-positive and negative strains), antioxidant (2,2-diphenyl-1-picrylhydrazyl and others), and antiproliferative (HeLa, A43, and MCF7 cell lines) potential. Hispidulin, luteolin, and tracin, isolated from C. arvense were reported to be with antibacterial potential. Based on its bioactive components, a proposed mechanism for antibacterial action is also highlighted. A toxicity study revealed that the aerial parts of C. arvense are toxic (LC50 of 51 μg/ml). Bioprospecting of this weed after detailed follow-up studies will help manage C. arvense in the future.
Keywords: Antioxidant, antimicrobial, antiproliferative, phytoconstituents, bioprospecting